Kebijakan Pembangunan Pariwisata Berkelanjutan Di Kabupaten Buleleng Selama Pandemi Covid-19 - Nyoman Dane (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Nowadays tourism as one of the drivers of the world economy has positive and negative roles for the survival of nature. The rapid spread of COVID-19 has prompted the government to make various efforts to contain the spread of COVID-19. The implication of this condition has a direct impact on the tourism industry in Buleleng Regency. Based on the problems described, this study aims to examine policies for sustainable tourism development in Buleleng Regency during the Covid-19 pandemic. The method used in this research is descriptive qualitative method. Data as the basic source of analysis in this study were obtained by using the documentary study data collection technique. This data will then be processed through three stages consisting of data reduction, data presentation / display and drawing conclusions. Based on the results of the study, it was concluded that the tourism sector, which was slumped due to the Covid-19 pandemic, is entering a new normal era. Sustainable tourism will be a consequence of the part of tourism development, after the Covid-19 pandemic is over. Sustainable tourism work is not only sectoral work, but must be comprehensive, whether it be the community, government, academics and others, or what is commonly called pentahelix. Keywords: Sustainable Tourism Development Policy and Covid-19